Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Dalam Materi Menulis Paragraf Berdasarkan Gambar Seri Melalui Metode Diskusi Dikelas IIIB SD Negeri 008 Rambah Hilir - asni Asni (STKIP Rokania Pasir Pangaraian, 2018)
Abstract, This study aims to improve the learning outcomes of Bahasa Indonesia about the material to write paragraphs based on the drawing series through the discussion method class III B SD Negeri 008 Rambah Hilir. The subjects of this study are the students of class III B SD Negeri 008 which amounted to 22 students. Action research is carried out in 2 cycles. Data collection in this study using test and observation methods. The data of research results on the material of writing paragraphs based on series drawings. The result of the research shows that learning by using serial drawing media can improve student learning result of class III B SD 008 Rambah Hilir, which in the initial condition of result before given action average value 5,98. In the first cycle using the media image of the series there is an increase so that the average grade value becomes 6.62. In the second cycle showed an increase with the average obtained 7.62.